Wastage of Timber at Tree Harvesting Stage in South India - Rao, D. S.; Singh, B. P. (Indian Forester, 1991)
The present study of wastage of timber at tree harvesting stage in South India reveals an avoidable wastage of about 6% of the volume of tree. Reduction in wastage by use of proper tools of IS standards and their proper maintenance along with training of staff and workers in Basic Logging Techniques with co-operation of Forest Department and Corporations is absolutely essential.